**Chapter 1 Grade 7 Integer Review**

(+4) + (-4) = 0

have 4 owe 4

*Brackets are training wheels. Pure standard form: 4 - 4-

Zero pair = When subtracting something that isn't there, use a zero pair.

Examples of zero pairs: +6 -6, +10 -10, +19 -19, +16 -16, +11-11,+14 -14, +63 -63

-3 -2 = 3-2 = subtraction = adding a negative integer.

5. -3 - (-7) = +4

6. -3 - 7 = -10

have 4 owe 4

*Brackets are training wheels. Pure standard form: 4 - 4-

Zero pair = When subtracting something that isn't there, use a zero pair.

Examples of zero pairs: +6 -6, +10 -10, +19 -19, +16 -16, +11-11,+14 -14, +63 -63

-3 -2 = 3-2 = subtraction = adding a negative integer.

5. -3 - (-7) = +4

6. -3 - 7 = -10

7. 3 - 7 = -4

8. 3 + 7 = 10

9. -3 + 7 = -4

Chapter 2 Multiplying Integers

(+2) x (-3)=

*-6***or**2 groups of (-3)(-2) x (+3)=

*-6*The negative sign on the first integer is saying to remove 2 groups of (+3)

Sign Rule (negative signs)

Even = When you have an even number of negatives factors the product is POSITIVE.

Odd = When you have an odd number of negative factors the product is negative.

Homework: 290-292 1-19 odds

HWB: 8.1 90-91

**Chapter 3 Dividing Integers**

*2 types of division:*

6/3 =

*How many groups of (+3) are in 6?*Paratative division or making parts.

6/3=2 Share 6 with 2 groups

Quotative division or sharing your total with groups

(-6)/(-3)=2

How many groups of (-3) are in (-6)?

**2 groups***Only partative will work.

6/3=2

2x3=6

2x3=6

3x2=6

(-6)/(-3)=2

2x(-3)=-6

(-3)x(2)=-6

If you have no negative or an even number of negative signs in a division question the quotient is positive. When you have an odd number of (-) signs in a division question the quotient is negative.

HWB: 96 & 97

**Chapter 4 Great Big Book of Integers**

How I would solve this equation: (+5) x (-3) + (-6) / (+3)

First, I would follow the rules of BEDMAS, so I'd put square brackets around (-6) / (+3)

After, I would solve what (+5) x (-3)

Then I would add the two answers together which would equal to

**-17.**(+5) x (-3) + [(-6) / (+3)]

-15 + -2

= -17

## No comments:

## Post a Comment